Targeting the disrupted Hippo signaling to prevent neoplastic renal epithelial cell immune evasion - Xiangmin Lv; Jiyuan Liu; Jinpeng Ruan; Peichao Chen; Chunbo He; Xingeng Zhao; Cong Huang; Li Chen; Hongbo Wang; Guohua Hua; Davie Shi; Siyi Yang; et al. (Nature Communications)
Abstract Large-scale cancer genetic/genomic studies demonstrated that papillary renal cell carcinoma (pRCC) is featured with a frequent shallow deletion of the upstream tumor suppressors of the Hippo/YAP signaling pathway, suggesting that this signaling pathway may play a role in pRCC development. Here we develop a transgenic mouse model with a renal epithelial cell-specific hyperactivation of YAP1 and find that hyperactivation of YAP1 can induce dedifferentiation and transformation of renal tubular epithelial cells leading to the development of pRCC. We analyze at the single-cell resolution the cellular landscape alterations during cancer initiation and progression. Our data indicate that the hyperactivated YAP1, via manipulating multiple signaling pathways, induces epithelial cell transformation, MDSC (Myeloid-derived suppressor cells) accumulation, and pRCC development. Interestingly, we find that depletion of MDSC blocks YAP1-induced kidney overgrowth and tumorigenesis. Inhibiting YAP1 activity with MGH-CP1, a recently developed TEAD inhibitor, impedes MDSC accumulation and suppresses tumor development. Our results identify the disrupted Hippo/YAP signaling as a major contributor to pRCC and suggest that targeting the disrupted Hippo pathway represents a plausible strategy to prevent and treat pRCC.